Cephalometric assessment of maxillary length in Serbian children with skeletal class III - Stojanović Zdenka; Nikolić Predrag; Nikodijević Angelina; Milić Jasmina; Stojanović Branislav (Vojnosanitetski Pregled)
Background/Aim. Malocclusion of skeletal class III is a complex irregularity of sagittal inter-jaw relationship, which is due to irregularities of sagittal position of one or both of the jaw bones, which is often associated with disproportionate ratio of their length. The aim of this study was to determine whether the length of the jaw of children with skeletal class III in the period of mixed dentition was changed. Methods. Fifty children with skeletal class III and the same number of those with skeletal class I, of both sexes, have been selected on the basis of cephalometric analysis of profile tele-x-ray of the head. All the children aged 6-12 had mixed dentition, and were divided according to sex and age into three subgroups within each group. The length of maxilla, mandible and cranial base were measured. Proportions among the lengths measured within each group were found and difference significance in the measured lengths and their proportions among groups and subgroups were evaluated. Results. The children with skeletal class III, compared with the findings in the control group, had significantly lower values of maxillary length, total maxillary length, as well as lower values of their lengths in proportion to lengths of the front or the total length of cranial base and in proportion to mandibular lengths (p < 0.05). Among the patients of different sexes, both in the test and the control group, a significant difference in the values of the measured lengths was found. Conclusion. The children with skeletal class III have significantly shorter maxilla than those with skeletal class I.